2017
DOI: 10.21037/jtd.2017.06.67
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cryopreservation on tracheal allograft antigenicity in dogs

Abstract: Background: Prolonged cryopreservation (~8-10 months) has been shown to reduce the antigenicity of tracheal allografts due to subsequent denuding of epithelium. In the present study, tracheal epithelium was assessed after variable periods of cryopreservation. Immunosuppressant-free allotransplantation was then undertaken to evaluate the impact of cryopreservation on tracheal antigenicity in dogs. Methods: Tracheal rings [7][8] were removed from mongrel adult dogs for cryopreservation (1-10 months, −85 ℃) and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…CryoT and DecellT grafts were preliminarily compared by H&E for an overall overview on tissue organization and/or evidence of eventual modification/disruptions. Cryopreservation only caused a partial exfoliation of the respiratory epithelium, in accordance with many other studies reported in the literature [ 24 , 60 , 83 , 97 ]. In accordance with Nakanishi et al [ 83 ] it is possible that partial maintenance of epithelial cells in tracheal allografts, eventually capable of survival, may be ascribed to cryoprotection itself.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…CryoT and DecellT grafts were preliminarily compared by H&E for an overall overview on tissue organization and/or evidence of eventual modification/disruptions. Cryopreservation only caused a partial exfoliation of the respiratory epithelium, in accordance with many other studies reported in the literature [ 24 , 60 , 83 , 97 ]. In accordance with Nakanishi et al [ 83 ] it is possible that partial maintenance of epithelial cells in tracheal allografts, eventually capable of survival, may be ascribed to cryoprotection itself.…”
Section: Discussionsupporting
confidence: 91%
“…The first preclinical study (pig) reporting about cryopreserved tracheal graft implantation in orthotopic position was described by Lenot et al [ 68 ]. Despite surgery failure due to inadequate blood supply, the histologic structures and the mechanical properties were well preserved, stimulating intense research on this substitute type [ 15 , 24 , 26 , 28 , 38 , 60 , 61 , 67 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ]. Hence, focusing on freezing temperature and liquid nitrogen storage, cryopreserved tracheal graft protocols can be distinguished into two groups: (a) freezing at −60° to −140 °C and storage in liquid nitrogen until use; (b) freezing at −80°/−85 °C, without recurring to liquid nitrogen storage [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is no doubt that the cryopreserved homograft is immunogenic as the cryopreserved technology retained lots of allogeneic cells ( 29 ). The graft-related immune response plays an important role in the failure of cryopreserved homograft in young children ( 38 ).…”
Section: Clinical Outcomes Of Available Conduitsmentioning
confidence: 99%